2024
DOI: 10.1002/eji.202350669
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in adipose tissue macrophages prevents diet‐induced inflammation and metabolic dysregulation

Eleni Siouti,
Maria Salagianni,
Maria Manioudaki
et al.

Abstract: The importance of macrophages in adipose tissue (AT) homeostasis and inflammation is well established. However, the potential cues that regulate their function remain incompletely understood. To bridge this important gap, we sought to characterize novel pathways involved using a mouse model of diet‐induced obesity. By performing transcriptomics analysis of AT macrophages (ATMs), we found that late‐stage ATMs from high‐fat diet mice presented with perturbed Notch signaling accompanied by robust proinflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…One previous study showed that IL-12 and TNFa levels in the plasma were increased in PCOS patients compared to controls (37), and another study revealed the correlation Notch signaling is reported to be activated in GCs in PCOS and regulates aberrant cumulus-oocyte complex (COC) expansion, which may lead to ovulatory dysfunction (41). It was also involved in adipose tissue inflammation and metabolic dysregulation (42). TUT4 belongs to RNA terminal uridyltransferases, and it has been suggested to play a role in post-transcriptional regulation of inflammation based on in vitro studies (43).…”
Section: Discussionmentioning
confidence: 99%
“…One previous study showed that IL-12 and TNFa levels in the plasma were increased in PCOS patients compared to controls (37), and another study revealed the correlation Notch signaling is reported to be activated in GCs in PCOS and regulates aberrant cumulus-oocyte complex (COC) expansion, which may lead to ovulatory dysfunction (41). It was also involved in adipose tissue inflammation and metabolic dysregulation (42). TUT4 belongs to RNA terminal uridyltransferases, and it has been suggested to play a role in post-transcriptional regulation of inflammation based on in vitro studies (43).…”
Section: Discussionmentioning
confidence: 99%
“…Notch1, as an inflammatory marker protein, exerts regulatory effects on obesity development. Previous studies have demonstrated that the activation of Notch1 signaling promotes adipocyte proliferation [ 19 ], while the modulation of the Notch1 signal in adipose tissue macrophages is crucial for regulating inflammation and metabolism [ 20 ]. Moreover, inhibiting Notch1 expression has been shown to significantly enhance brown fat thermogenesis, promote white fat browning, and ameliorate obesity [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%